Nationwide gastric cancer prevention in China, 2021–2035: a decision analysis on effect, affordability and cost-effectiveness optimisation. Issue 12 (28th July 2022) - Wang, Zixing; Han, Wei; Xue, Fang; Zhao, Yujie; Wu, Peng; Chen, Yali; Yang, Cuihong; Gu, Wentao; Jiang, Jingmei
Abstract : Objective: To project future trajectories of the gastric cancer (GC) burden in China under different scenarios of GC prevention and identify strategies to improve affordability and cost-effectiveness. Design: Using a cohort of Chinese men and women born during 1951–1980, we assumed that different prevention strategies were conducted, including eradication of Helicobacter pylori (Hp) and endoscopy screening (one-time, annual, biennial, triennial or stratified according to personal risk). We performed a literature search to identify up-to-date data and populate a Markov model to project the number of new GC cases and deaths during 2021–2035, as well as resource requirements and quality-adjusted life-years (QALYs). We examined the impacts of general (among the whole population) and targeted (high-risk population) prevention. Results: During 2021–2035, 10.0 million new GC cases and 5.6 million GC deaths would occur, with 7.6%–35.5% and 6.9%–44.5%, respectively, being avoidable through various prevention strategies. Relative to the status quo, Hp eradication was a cost-saving strategy. General annual screening dominated other screening strategies, but cost more than CNY 70 000 per QALY gained (willingness-to-pay) compared with Hp eradication. Among endoscopy strategies, targeted screening resulted in 44%–49% lower cost per QALY gained over the status quo than general screening. Among high-risk population, tailoring the screening frequency according to personal risk could reduce endoscopy-related resources by 22% compared with biennial screening and by 55% compared with annual screening, Conclusion: Our findings provide important input for future decision-making and investment, highlighting the need and feasibility for China to include GC prevention in its national health plans.